2006
DOI: 10.1002/jctb.1381
|View full text |Cite
|
Sign up to set email alerts
|

Sintering‐induced aromatization during n‐heptane reforming on Pt/Al2O3 catalysts

Abstract: A platinum/alumina catalyst was sintered in oxygen and hydrogen atmospheres using two metal loadings of the catalyst: 0.3% Pt and 0.6% Pt. After sintering, the aromatization selectivity was investigated with the reforming of n-heptane as the model reaction at a temperature of 500• C and a pressure of 391.8 kPa. The primary products of n-heptane reforming on the fresh platinum catalysts were methane and toluene, with subsequent conversion of benzene from toluene demethylation. To induce sintering, the catalysts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Using a cyclic oxidative/reductive process, it was found that at all studied temperatures (500–800 °C), the particle sizes of Pt were smaller after the oxidation step (2.21–9.56 nm) compared with the Pt particle size after the reduction (3.03–11.11 nm), although the particle size even after reduction was still smaller than that observed for the fresh catalyst . Similar trends were noted in other studies of the same monometallic Pt catalyst . It should, however, be noted that this was quite a prolonged reduction step (16 h at 150 °C and 2 h at 250 °C) in pure hydrogen.…”
Section: Metal Redispersion Strategiessupporting
confidence: 80%
See 1 more Smart Citation
“…Using a cyclic oxidative/reductive process, it was found that at all studied temperatures (500–800 °C), the particle sizes of Pt were smaller after the oxidation step (2.21–9.56 nm) compared with the Pt particle size after the reduction (3.03–11.11 nm), although the particle size even after reduction was still smaller than that observed for the fresh catalyst . Similar trends were noted in other studies of the same monometallic Pt catalyst . It should, however, be noted that this was quite a prolonged reduction step (16 h at 150 °C and 2 h at 250 °C) in pure hydrogen.…”
Section: Metal Redispersion Strategiessupporting
confidence: 80%
“…16 Similar trends were noted in other studies of the same monometallic Pt catalyst. 85 It should, however, be noted that this was quite a prolonged reduction step (16 h at 150 °C and 2 h at 250 °C), in pure hydrogen. Consequently, the fact that some sintering occurred during this reduction step is not surprising.…”
Section: Platinummentioning
confidence: 99%
“…It is posited that the sintered bimetallic catalyst contains a favourable structure for aromatic selectivity -a cuboctahedral structure of 6-atom (111) planes. 16,51 …”
Section: Role Of Carbonaceous Depositsmentioning
confidence: 98%
“…15 A second paper explored these effects for two different Pt loadings on Al 2 O 3 . 16 These studies were carried out in a microcatalytic reactor where the reforming of n-heptane was chosen as the model reaction.…”
Section: Introductionmentioning
confidence: 99%